Single‐crystal neutron diffraction in diamond anvil cells with hot neutrons. Issue 2 (21st February 2018) - Grzechnik, Andrzej; Meven, Martin; Friese, Karen
Abstract : It is shown that it is possible to perform single‐crystal measurements in diamond anvil cells with a monochromatic beam at modern hot neutron sources. The data are of very good quality and can be used for a full and reliable structure refinement. Abstract : It is demonstrated that it is possible to perform single‐crystal measurements in diamond anvil cells (DACs) with a monochromatic beam at modern hot neutron sources that offer the benefit of short neutron wavelengths with high fluxes. A piston–cylinder DAC with conical Boehler–Almax diamonds that allows for a wide accessibility of the reciprocal space has been developed. The diffraction data collected in this cell using hot neutrons are of very good quality and can be used for a full and reliable structure refinement.